Sleeve Gastrectomy and Liver Omentoplasty Can Increased Il-10 and TGF-Β Expression on Liver Fibrosis in Obesity - Purnamasari, Primadita; Nugroho, K. Heri; Prasetyo, Sigit Adi; Prajoko, Yan Wisnu; Haningtyas, Fatmala; Mukti, Sindu Nugroho; Saputro, Addy; Rozy, Abdul Mughni (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Obesity is a risk factor happening liver fibrosis because it makes presence of oxidative stress and inflammation that has role on pathogenesis and hepatic fibrosis progression. Until this moment, liver disease management still focused for treat disease primary, the most rational management of liver fibrosis is liver transplant, however number success transplant liver lower from on transplant kidneys, only 70-80% of recipients survived for at least 1 year, so that sleeve gastrectomy and liver omentoplasty procedure could become a choice for treating liver fibrosis on obese patients. AIM: This study aims to investigate correlation between sleeve gastrectomy and omentoplasty on TGF-β and IL-10 in obese rats with liver fibrosis METHOD: This study used a true experiment in-vivo design on male Wistar rat (Spargue Dawley) 4-6 weeks of age. Samples were divided into groups that includes normal control group, positive control group, group with sleeve gastrectomy, and group with both liver liver omentoplasty and sleeve gastrectomy. The level of TGF-β and IL-10 will be measured for descriptive and hypothesis analysis. RESULT: There is an increased level of IL-10 and TGF-β. Statistical analysis result shows a significant increase of IL-10 and TGF-β expression between normal group and control group with group given treatment sleeve gastrectomy and liver liver omentoplasty (p<0.05). CONCLUSION: liver Liver omentoplasty and sleeve gastrectomy procedure on obese mice with liver fibrosis could increases IL-10 expression but could not reduce (TGF-β expression).